Economic Exposure of Industrial Sectors on the Indonesia Stock Exchange Before and After the COVID-19 Pandemic - Mochamad Taufiq; Marius Pramana; Anastasia Lipursari (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the presence or absence of economic exposure in the industrial sector on the Indonesia Stock Exchange (IDX) before and after the Covid-19 pandemic. It also examines differences in economic exposure patterns between the two periods. The sample used was weekly data on the Composite Stock Price Index (CSPI) returns, the exchange rate (Rupiah against the US Dollar) returns and the stock price index of industrial companies returns on the IDX from March 2018 to February 2020 and March 2023 to June 2025. The analysis method used was multiple regression and the Chow test. The results indicate that economic exposure occurred during and after the economic crisis in the consumer goods industry, not due to the exchange rate but to the CSPI returns. The results of the Chow test indicate there are differences in the influence pattern between the periods during and after the Covid-19 pandemic.